Evaluation of the 8th edition American Joint Commission on Cancer (AJCC) staging system for patients with intrahepatic cholangiocarcinoma: A surveillance, epidemiology, and end results (SEER) analysis. Issue 6 (12th June 2017) - Kim, Yuhree; Moris, Dimitrios P.; Zhang, Xu‐Feng; Bagante, Fabio; Spolverato, Gaya; Schmidt, Carl; Dilhoff, Mary; Pawlik, Timothy M.
Abstract : Background: The objective of this study was to assess the prognostic performance of American Joint Committee on Cancer (AJCC) 8th edition in patients with intrahepatic cholangiocarcinoma (ICC) using a cancer registry. Methods: The Surveillance, Epidemiology, and End Results (SEER) cancer registry was queried to identify 1008 patients who underwent surgical resection of ICC during 1998‐2013. Kaplan‐Meier method and Cox proportional hazards regression models were used to analyze long‐term survival. The relative discriminative abilities were assessed using the Harrell's concordance index. Results: Median patient age was 62 years and 47.6% of the patients were male. Most tumors were T1 or T2 ( n  = 413, 41.0% and n  = 329, 32.6%, respectively) and 22.1% of patients had lymph node (LN) metastasis. Median tumor size was 5.5 cm. With a median follow‐up of 18 months, median survival was 27 months and 5‐year OS was 30.6%. The OS c‐index for the AJCC 8th staging system was 0.669, which was comparable with the c‐index for the 7th edition AJCC staging system (c‐index: 0.667); the AJCC 8th‐edition did provide more discrete stratification of patients. Conclusions: The new AJCC 8th‐edition staging system for ICC was largely comparable to the 7th‐edition version and did not provide a marked improvement in overall prognostic discrimination.